MicroRNA-21 and PDCD4 expression during in vitro oocyte maturation in pigs. Issue 1 (December 2016) - Wright, Elane; Hale, Benjamin; Yang, Cai-Xia; Njoka, Josephat; Ross, Jason
Abstract Background MicroRNA (miRNA) are small non-coding RNA molecules critical for regulating cellular function, and are abundant in the maturing oocyte and developing embryo. MiRNA-21 (MIR21) has been shown to elicit posttranscriptional gene regulation in several tissues associated with rapid cell proliferation in addition to demonstrating anti-apoptotic features through interactions withPDCD4 mRNA and other targets. In many tissues, MIR21 interacts and suppresses PDCD4 due to the strong complementation between MIR21 and thePDCD4 3′UTR. Methods The objective of this project was to examine the relationship between MIR21 and PDCD4 expression in porcine oocytes during in vitro maturation and assess the impact of MIR21 inhibition during oocyte maturation on early embryo development. Additionally, we evaluated the effect of gonadotropins in maturation media and the presence of cumulus cells to determine their ability to contribute to MIR21 abundance in the oocyte during maturation. Results During in vitro maturation, expression of MIR21 increased approximately 6-fold in the oocyte and 25-fold in the cumulus cell. Temporally associated with this was the reduction of PDCD4 protein abundance in MII arrested oocytes compared with GV stage oocytes, althoughPDCD4 mRNA was not significantly different during this transition. Neither the presence of cumulus cells nor gonadotropins during in vitro maturation affected MIR21 abundance in those oocytes achieving MII arrest. However, inhibition of MIR21 activity during in vitro maturation using antisense MIR21 suppressed embryo development to the 4–8 cell stage following parthenogenetic activation. Conclusions MIR21 is differentially expressed in the oocyte during meiotic maturation in the pig and inhibition of MIR21 during this process alters PDCD4 protein abundance suggesting posttranscriptional regulatory events involving MIR21 during oocyte maturation may impact subsequent embryonic development in the pig.